The Difference between the N60 and BK77 Height Systems - Jürgenson, Harli; Kall, Tarmo (Nordic Journal of Surveying and Real Estate Research, 2004)
This paper investigates the difference between the Finnish height datum N60 and the 1977 Baltic height system (BK77). The method used is comparison of the gravimetric and geometric geoid heights. It is important to determine the difference since there is still no precise levelling connection between the two countries. Finding the correct epoch for BK77 is a little problematic; some investigations made are described in this paper. All the new gravimetric data digitised over the last few years were used in the gravimetric geoid calculation, along with 110,000 points from north Estonia (measured by the Geological Survey of Estonia) and data from the area embracing Lake Peipsi and the adjoining parts of Russia. Also aerogravimetric measurements above the Gulf of Finland were used. The gravimetric geoid calculation method employed was remove-restore with FFT. The new gravimetric data contributed to getting a gravimetric geoid surface that was more precise. About 27 GPS-levelling points from Estonia and Finland were used for determining the difference between the height systems. The GPS points were taken from the first order net with precise orthometric, or normal, heights. Normal/orthometric heights were corrected for land uplift. A very small tilt could be observed between the gravimetric and the geometric geoid. The results showed that the difference between the geoids is similar in both Finland and Estonia, which means that the difference between the height systems is small, about 3 cm.